Unidirectional transport of IgG by neonatal Fc receptor in human thyrocytes varies across different IgG subclasses. (5th December 2018) - Zhao, Chenxu; Gao, Ying; Yu, Nan; Li, Tiancheng; Zhang, Yang; Zhang, Hong; Lu, Guizhi; Gao, Yanming; Guo, Xiaohui
Abstract: Neonatal Fc receptor (FcRn) is down-regulated in Hashimoto's thyroiditis (HT) thyrocytes and mediates IgG endocytosis in thyrocytes. The serum distribution of IgG subclasses (of TgAb and TPOAb) differs between HT patients and normal individuals. We aimed to explore the direction and regulation of FcRn-mediated IgG transport in thyrocyte monolayers and the difference between various IgG subclass transport. IgG was transported by FcRn from the basolateral to apical side in the thyrocyte monolayers grown on Transwell filters and the transport was inhibited by IFN-γ and TNF-α. Stimulation by T3 and TSH down-regulated FcRn expression in thyrocytes. IgG1 was transported preferentially over IgG2 and IgG4, which might be related to the differences in FcRn-binding affinities as shown by SPR. FcRn mediates unidirectional IgG transport in thyrocytes in a tissue-specific manner. Down-regulation of FcRn is speculated to play a protective role in HT pathogenesis by mainly reducing IgG1 transport in thyrocytes. Highlights: In thyrocyte monolayers, IgG is transported by FcRn unidirectionally from the basolateral side to apical side. Triiodothyronine and thyroid-stimulating hormone down-regulate FcRn expression. IgG subclasses are competitively transported by FcRn likely because of affinities. FcRn down-regulation may have a protective role in Hashimoto's thyroiditis.